أثر تغيّر قيمة النقود على الحقوق والالتزامات الآجلة - هاجر, مجيدي; خديجة, خزان (جامعة الوادي university of eloued, 2023)
للنقود دور هام في حياة الناس والمجتمعات البشرية.كما أن لها دورا اساسيا ومحوريا في النظام الاقتصادي .ويتعرض الاقتصاد إلى العديد من المشكلات والنكسات التي تترك الأثر البليغ في استقراره وأحواله، وبالتالي ينعكس ذلك على الوضع الاقتصادي المنقلب على الأوضاع المعيشية، والتجارية لأفراد المجتمع، وتبرز مشكلة انخفاض قيمة النقود كإحدى هذه المشكلات التي تصيب الاقتصاد، وهو ما يطلق عليه التضخم حيث تنخفض قيمة النقود مقابل ارتفاع سعر السلع والمواد، يؤثر هذا الانخفاض لقيمة النقود على معاملات الناس وبيعهم بالأجل أو الديون التي لهم في ذمم الاخرين فيأتي موعد القرض أو البيع بالأجل وقد تبدلت قيمة النقود من حيث قوتها وقيمتها الحقيقية، فيكون المدفوع عند حلول الأجل غير مساو أو مكافئ للمدفوع في أول العقد وبداية التعامل فيقع الغبن الكبير على أحد طرفي العقد دون تقصير أو سبب منه، فهل هناك اعتبار لتبدل قيمة النقود ارتفاعا أو انخفاضا في سداد الديون أو الحقوق المترتبة في الذمة أم لا ؟ تعددت أقوال العلماء في هذه المسألة: فمنهم من قالوا: بوجوب ارجاع المثل، والبعض الآخر قالوا: برد القيمة، ومنهم من فرق بين الاختلاف اليسير والكبير في قيمة النقود، ومنهم من جعل الخسارة مناصفة بين طرفي العقد. Money has an important role in the lives of people and human societies. It also has a basic and pivotal role in the economic system. The economy is exposed to many problems and setbacks that leave a profound impact on its stability and conditions. And thus this is reflected in the economic situation that is upended on the living and commercial conditions of members of society. The problem of the decline in the value of money is one of these problems that affect the economy. This is called inflation, where the value of money decreases in exchange for the increase in the price of goods and materials. This decrease in the value of money affects people’s transactions and selling them on credit. The value of the money has changed in terms of its strength and its real value. So the payment at the end of the term is not equal or equivalent to the one paid at the beginning of the contract and the beginning of the transaction. So the great injustice falls on one of the parties to the contract without negligence or cause from it. Debts or rights in the custodianship or not? There are many scholars’ sayings on this issue: some of them said: It is necessary to return the same. Others said: refund the value. And some of them made a difference between the slight and the big difference in the value of money. And some of them made the loss equally between the two parties to the contract.
مدكرة
Keywords: التغير. القيمة . النقود . الدين . التضخم . الانكماش.; the change . the value . money. Religion . inflation. deflation.